2015
DOI: 10.1155/2015/913152
|View full text |Cite
|
Sign up to set email alerts
|

Antiedematogenic Evaluation ofCopaifera langsdorffiiLeaves Hydroethanolic Extract and Its Major Compounds

Abstract: Inflammatory disorders affect many people worldwide, and medicinal plants are used to ameliorate these health problems. This paper reports the antiedematogenic and analgesic evaluation of Copaifera langsdorffii Desf. leaves hydroethanolic extract (Cop) and two of its isolated compounds: quercetin-3-O-α-l-rhamnopyranosyl (quercitrin) and kaempferol-3-O-α-l-rhamnopyranosyl (afzelin). For that, the following experimental protocols were undertaken locomotor performance, writhing induced by acetic acid, antinocicep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
13
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 26 publications
5
13
0
1
Order By: Relevance
“…In the carrageenan-induced paw edema test (Figure 3), it is observed that indomethacin significantly reduced the volume of the edema, as expected (Furtado et al, 2015;dos Santos et al, 2010). The dose of 10 mg/kg was significantly different from the negative control in the fourth hour of evaluation, showing the anti-inflammatory potential of kaempferide.…”
Section: Resultssupporting
confidence: 79%
See 2 more Smart Citations
“…In the carrageenan-induced paw edema test (Figure 3), it is observed that indomethacin significantly reduced the volume of the edema, as expected (Furtado et al, 2015;dos Santos et al, 2010). The dose of 10 mg/kg was significantly different from the negative control in the fourth hour of evaluation, showing the anti-inflammatory potential of kaempferide.…”
Section: Resultssupporting
confidence: 79%
“…Thus, the effect of kaempferide may be correlated with inhibition on modulatory pathways of the arachidonic acid cascade, such as prostaglandins, cyclooxygenase products, and nitric oxide (NO). On the other hand, it is not correlated to mediators such as histamine, serotonin, and bradykinin on vascular permeability (Furtado et al, 2015). The modulation on inflammatory pathways of green propolis extract is reported in the literature, and the extract rich in artepillin C and kaempferide modulates the expression of different mediators, such as NO and several cytokines (Szliszka et al, 2013).…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Copaifera langsdorffii is particularly important in Brazil because it is widely distributed throughout the country and is used in popular and indigenous knowledge as a healing and anti-inflammatory agent (Corrêa, 1984;Veiga & Pinto, 2002). Due to its use in popular medicine since the 16 th century, studies have reported several biological activities related to the Copaifera langsdorffii oil-resin and leaves extract, as well as skin wound healing (Gushiken et al, 2017a;Lemos et al, 2015;Masson-Meyer et al, 2013), anti-microbial activity (Abrão et al, 2015), gastrointestinal diseases treatments (Gomes et al, 2007;Lemos et al, 2015;Paiva et al, 2002), antiedematogenic (Furtado et al, 2015), antinociceptive (Gomes et al, 2007) and urolithiasis treatment (Brancalion et al, 2012;Oliveira et al, 2013). However, there are few studies reporting copaiba effects in horse skin wound healing (Lucas et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…O extrato hidroalcoólico das folhas também reduziu a formação de edema em dois modelos de estudo, cujo efeito anti-inflamatório foi associado à regulação de mediadores como a serotonina, e à liberação de óxido nítrico (Furtado et al 2015).…”
Section: Figura 1 -Estruturas Químicas Dos Flavonoides Majoritários Nunclassified